Knowledge and Attitude Regarding Advance Directives for End of Life Care Among Physicians and Nurses - บุสษา, พิชรา; พรพิบูลย์, พิกุล; สิทธิสมบัติ, สุดารัตน์ (Nursing Journal CMU, 2019)
The purpose of this descriptive study was to describe the knowledge and attitudes regarding advance directives for end of life care among physicians and nurses. The study sample consisted of 209 medical doctors and 316 nurses working at a university hospital. The instruments used in this study included the demographic data recording form, the Knowledge Regarding Advance Directives for End of Life Care questionnaire, and the Attitude Regarding Advance Directive for End of Life Care questionnaire. These instruments were developed by the researcher based on the National Health Act 2550, Section 12 and after reviewing literature regarding advance directives. The content validity and reliability were ascertained for all instruments. Data were analyzed using descriptive statistics. The study results revealed that More than half of physicians (52.15 %) had knowledge regarding advance directives for end of life at a high level, while 36.85 % had a moderate level of knowledge. Most nurses (73.10 %) had a high level of knowledge regarding advance directives for end of life, while 25.30 % had a moderate level of knowledge. More than half of physicians (55.50 %) had a moderate level of attitude regarding advance directives for end of life, while 44.50 % had a high level. Most nurses (62.66 %) had a moderate level of attitude regarding advance directives for end of life, while 37.34 % had a high level. The findings of this study can be used as a baseline for further development about the knowledge and attitudes of physicians and nurses regarding advance directives. These findings highlight the need for interventions to promote knowledge and attitudes among health personnel. Further research should be done to identify effective interventions for promoting knowledge and attitudes among physicians and nurses.